Some oral microbiota in complete cleft infants in comparison with normal infants - Rula Qays Abdulkareem Al-Humairi; Zainab Juma Jafar (Journal of the Pakistan Medical Association, 2024)
Objective: To compare caries-related microorganisms and candida in complete cleft infants with normal palate infants. Method: The case-control study was conducted from April 2021 to January 2022 at the College of Dentistry, University of Baghdad, Baghdad, Iraq, and comprised infants with age ranging from 1 day to 4 months. They were divided into complete cleft group A and control group B. Group A was subdivided into those with class III Veau’s palatal classification, and the rest with class IV Veau’s palatal classification. Samples were taken using oral swab which were subjected to colony morphology, gram staining and biochemical testing. Data was analysed using SPSS 21. Result: Of the 52 subjects, 26(50%) were in each of the 2 groups. The subgroups of group A had 13(50%) patients each. The counting and colonisation of streptococcus mutans, lactobacilli and candida albicans were significantly higher in group A than in group B (p<0.05). The difference between the subgroups of group A was not significant (p>0.05). Conclusion: Infants with cleft palate were more susceptible to dental caries and oral infection than those with normal palate. Key Words: Candida albicans, Streptococcus, Cleft Palate, Dental, Lactobacillus, Staining